TANGGUNG JAWAB MANUSIA SEBAGAI KHALIFAH DI MUKA BUMI: PERSPEKTIF EKOTEOLOGI ISLAM TERHADAP KRISIS IKLIM GLOBAL - Syifa Adilla Zahra; Wiwin Sunita; Idham Kholid; Bambang Sri Anggoro; Mujib Mujib; Mardiyah Mardiyah (EDUPEDIA, 2026)
The threat of the global climate crisis is multidimensional and endangers the survival of humanity as well as the planet’s ecosystems. In the Islamic perspective, humans are positioned as khalifah (vicegerents) who bear moral and spiritual responsibility to preserve the balance of nature. This study aims to examine the concept of the khalifah’s responsibility within the framework of Islamic ecotheology and its relevance to the climate crisis. Using a library research method with a descriptive-analytical qualitative approach, this study analyzes classical Qur’anic exegesis literature, ecotheological thought, and contemporary environmental studies. The findings indicate that current environmental degradation contradicts the principles of tawhid (divine unity), amanah (trust), and mizan (balance). Islamic ecotheology offers a theocentric paradigm that integrates environmental preservation as both an act of worship and a moral obligation. Therefore, this study concludes that revitalizing ecological awareness grounded in Islamic values is an imperative step in responding to the climate crisis in an ethical and spiritual manner.